2020
DOI: 10.1080/1540496x.2020.1785425
|View full text |Cite
|
Sign up to set email alerts
|

Does the Indian Financial Market Nosedive because of the COVID-19 Outbreak, in Comparison to after Demonetisation and the GST?

Abstract: We investigate the impact of COVID-19 on the Indian financial market and compare it with the outcomes of two recent structural changes of the Indian economy: demonetization and implementation of the Goods and Services Tax (GST). Using daily stock return, net foreign institutional investment, and exchange rate data from January 3, 2003 to April 20, 2020, we find negative stock returns for all the indices during the COVID-19 outbreak, unlike during the post-demonetization and GST phases. Markov switching vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(92 citation statements)
references
References 36 publications
1
80
0
2
Order By: Relevance
“…Recent studies examine the impact of COVID-19 on the emerging stock markets. Mishra, Rath, and Dash (2020) find that all Indian stock indices react negatively to the COVID-19 outbreak. Salisu and Akanni (2020) also demonstrate that the global fear index (GFI) based on the cases and deaths from the COVID-19 is a good predictor of stock returns in the BRICS countries during the pandemic.…”
Section: Literature Review and Hypothesesmentioning
confidence: 84%
“…Recent studies examine the impact of COVID-19 on the emerging stock markets. Mishra, Rath, and Dash (2020) find that all Indian stock indices react negatively to the COVID-19 outbreak. Salisu and Akanni (2020) also demonstrate that the global fear index (GFI) based on the cases and deaths from the COVID-19 is a good predictor of stock returns in the BRICS countries during the pandemic.…”
Section: Literature Review and Hypothesesmentioning
confidence: 84%
“…Estrada, et al [60] explored ten major stock markets worldwide and cautioned that the effects of SARS-CoV-2 crisis may engender comparable impairment of the Crisis 1929, also being estimated a period between 9 and 12 months for recovery. Mishra, et al [61] revealed that all Indian stock market returns were negative during COVID-19 as compared with contemporary main structural changes such as demonetization and implementation of goods and services tax. In contrast, Bhuyan, et al [62] exposed that stock market returns of the SARS diseased nations displayed substantial rise related to the pre-SARS stage.…”
Section: Prior Research Regarding the Economic And Financial Consequementioning
confidence: 99%
“…Al-Awadhi et al (2020) found that daily growth in total COVID-19 confirmed cases and deaths have significant effects on stock returns across companies in China. In a study, Mishra et al (2020) found that all the stock market indices depicted downturn during COVID-19 in India and concluded from the Markov-Switching Vector Autoregressive (VAR) model that the impact is severe on stock returns. However, Ali et al (2020) observed that the plummets in stock market returns in China were relatively lower than that in the USA, the UK, Germany and South Korea, where market volatilities were larger.…”
Section: Literature Reviewmentioning
confidence: 99%